FILSAFAT MORAL IMMANUEL KANT: Suatu Tinjauan Paradigmatik - Islah Gusmian (UIN Raden Mas Said Surakarta, 2014)
The ethics taught in Pre-Kant era was eudemonistic. Thenature of moral proposed by Kant was the awareness of the obligation,absolute obligation. But there was no relationship between obligationand happiness. Actually Kant did not reject the acts which came frompositive feelings, but rejected the acts appeared from the feelings. Kantemphasized that the real moral awareness independently appear whenthere is no natural tendensi or social habit. If a person show his/ herhonesty from the deepest of his/ her heart, then he/she has the moralvalue. There is a possibility that being honest came from the socialoppression. Kant, also claimed that people obey and follow anobligation in which they do not have beliefs. Those are the reasons ofKant as quoted on the statement “das moralische Gesetz in mir“